(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Present experiment entitled “Effect of foliar spray of GA3 and NAA on growth, yield, and quality of cabbage (Brassica oleracea var. capitata L.)” was conducted during the Rabi season of 2023 - 24 at Agriculture Research Farm, Rama university, Mandhana, Kanpur. The experiment was laid out in Randomized Block Design (RBD) with three replications and nine treatments viz. T1 =Control, T2 =GA3 30 mg foliar spray at 30 DAT, T3 =GA3 60 mg foliar spray at 30 DAT, T4 =GA3 90 mg foliar spray at 30 DAT, T5 =GA3 120 mg foliar spray at 30 DAT, T6 =NAA 50 ppm foliar spray at 30 and 45 DAT, T7 =NAA 75 ppm foliar spray at 30 and 45 DAT, T8 =NAA 100 ppm foliar spray at 30 and 45 DAT, T9 =NAA 125 ppm foliar spray at 30 and 45 DAT. The result of the study revealed that the maximum plant height (29.5cm), leaf length (28.50cm), leaf width (27.78cm), Number of open leaves (12.5) stalk length (11.40cm) , minimum days of harvesting from transplanting( 90.40), head diameter ( 50.8 cm), head weight (1.30kg) yield/ ha (35.67q/ha), TSS content (4.43 º Brix), and acidity (2.50 %) was reported in treatment T9 (NAA 125 ppm foliar spray at 30 and 45 DAT) followed by treatment T8 = NAA (100 ppm) foliar spray at 30 and 45 DAT. Basis on these results treatment T9 can be suggested to the local farmer of Kanpur regions to obtain higher yield and better quality of cabbage.